All Things Bold and Beautiful: Researching Adult Learning Through Soaps - Paul Armstrong (Adult Education Research Conference, 2000)
This paper proposes that, globally, informal lifelong learning outside of education institutions is often neglected, and that cultures of learning must recognize and value a wide range of informal learning. In popular culture, soap operas have both intentionally and unintentionally been sites for learning, and their significance need to be more thoroughly researched. But this challenges conventional methodologies. Innovative approaches are needed, including the use of chat forums on the worldwide web, through the internet.